2022
DOI: 10.3389/fendo.2022.842722
|View full text |Cite
|
Sign up to set email alerts
|

Factors Defining the Association Between Vitamin D and Testosterone in Males With Type 2 Diabetes and Hypogonadism

Abstract: ObjectiveThis study aimed to evaluate Serum 25-hydroxyvitamin D (25[OH]D) levels in diabetic men with and without hypogonadism and figured out the potential factors influencing the connection between vitamin D and testosterone.MethodsA total of 367 men with type 2 diabetes mellitus (T2DM) were investigated, including 254 men with normal gonadal function (Group 1) and 113 men with hypogonadism (Group 2). Men with hypogonadism were classified as either hypogonadotropic hypogonadism (Group 2a) or hypergonadotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…In the present study, higher diabetes duration was observed in T2DM patients with hypogonadism than without hypogonadism. Zheng et al [26] and Hu et al [27] reported similar findings in their study on hypogonadism in type 2 diabetes mellitus patients. The higher prevalence of hypogonadism was mainly due to HbA1c and DM higher duration in underweighted T2DM patients.…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, higher diabetes duration was observed in T2DM patients with hypogonadism than without hypogonadism. Zheng et al [26] and Hu et al [27] reported similar findings in their study on hypogonadism in type 2 diabetes mellitus patients. The higher prevalence of hypogonadism was mainly due to HbA1c and DM higher duration in underweighted T2DM patients.…”
Section: Discussionsupporting
confidence: 65%